2019
DOI: 10.1016/j.freeradbiomed.2019.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen radical disease in the newborn, revisited: Oxidative stress and disease in the newborn period

Abstract: Thirty years ago, there was an emerging appreciation for the significance of oxidative stress in newborn disease. This prompted a renewed interest in the impact of oxygen therapy for the newborn in the delivery room and beyond, especially in premature infants. Today, the complexity of oxidative stress both in normal regulation and pathology is better understood, especially as it relates to neonatal mitochondrial oxidative stress responses to hyperoxia. Mitochondria are recipients of oxidative damage and have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 179 publications
(207 reference statements)
1
97
0
2
Order By: Relevance
“…In our research, we further found that maternal diabetes was also associated with PPHN. Newborn infants are at risk of oxidative stress after transitioning from the low oxygen environment, the uterus, to air (30). This process may be exacerbated by maternal diabetes mellitus, for the causal link between diabetic hyperglycemia and the production of reactive oxygen species (ROS) by mitochondria (31).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our research, we further found that maternal diabetes was also associated with PPHN. Newborn infants are at risk of oxidative stress after transitioning from the low oxygen environment, the uterus, to air (30). This process may be exacerbated by maternal diabetes mellitus, for the causal link between diabetic hyperglycemia and the production of reactive oxygen species (ROS) by mitochondria (31).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been recognized as a critical factor in the pathophysiology of PPHN (30). In lamb with PPHN induced by antenatal ligation of ductus arteriosus, the endothelium and vascular smooth muscle of the pulmonary arteries showed an elevated level of superoxide and H 2 O 2 (37), with decreased expression and activity in manganese SOD (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have been performed to investigate the efficacy of antioxidant therapies in preventing acute inflammatory injuries and ARDS. However, to date, there is no FDA approved treatment for patients receiving mechanical ventilation and hyperoxia who develop ALI/ARDS [39,40]. Recently, research has been directed toward dietary antioxidants, such as vitamin C and Nrf2-inducers.…”
Section: Antioxidants Are Effective In Mitigating Cellular Damage Andmentioning
confidence: 99%